Spatially-antisymmetric localization of matter wave in a bichromatic optical lattice - Cheng, Y. [UNESP]; Adhikari, Sadhan Kumar [UNESP] (Iop Publishing Ltd, 2010)
By direct numerical simulation of the time-dependent Gross-Pitaevskii equation using the split-step Fourier spectral method we study the double-humped localization of a cigar-shaped Bose-Einstein condensate (BEC) in a one-dimensional bichromatic quasi-periodic optical-lattice potential, as used in a recent experiment on the localization of a BEC [G. Roati et al., Nature 453, 895 (2008)]. Such states are spatially antisymmetric and are excited modes of Anderson localization. Where possible, we have compared the numerical results with a variational analysis. We also demonstrate the stability of the localized double-humped BEC states under small perturbation.
Keywords: Anderson localization; Bose-Einstein condensation; bichromatic optical lattice; antisymmetric localized state